ANALISIS KEBUTUHAN LEMBAR KERJA PESERTA DIDIK TERINTEGRASI STEM PADA MATERI KEANEKARAGAMAN HAYATI UNTUK KELAS X SMA/MA - Getri Yulanda; Yosi Laila Rahmi (Bioilmi: Jurnal Pendidikan, 2022)
One of the lessons that answers the needs of 21st century students is learning by applying the Science, Technology, Engineering, Mathematics (STEM) approach. The form of integrating the STEM approach in learning can be done through learning resources such as LKPD. This study aims to analyze the application of the STEM approach to biology learning. This research method uses a descriptive research type and uses a 4-D model. Data collection was carried out by observing 30 students and interviewing 1 Biology teacher. Qualitative data analysis was carried out by interviewing, collecting data, analyzing and concluding. The results of this study indicate that students need worksheets with an attractive appearance, besides attracting students they also need worksheets that demand critical, creative, innovative and collaborative thinking skills with the aim of directing students to solve problems in a project assignment that is in the worksheets, and the results appropriate to meet the needs of students, namely by analyzing the application of the STEM approach to biology learning.